PENATALAKSANAAN FISIOTERAPI PADA KONDISI OSTEOARTHRITIS GENU SINISTRA DENGAN MODALITAS ULTRASOUND, TRANSCUTANEUS ELECTRICAL NERVE STIMULATION DAN LATIHAN DENGAN METODE THERABAND DI RSUD KRATON KOTA PEKALONGAN - Citra Prima Pertiwi; Rendra Gita Aulia M.H (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2016)
Osteoarthritis (OA) is a degenerative joint disease, where the overall structure of the joints undergoes pathological changes. Characterized by the breakdown of cartilage (cartilage) hyalin joints, increasing the thickness and sclerosis of the bone plate, the growth of osteophytes on the banks of the joints, stretched joint capsule, the onset of inflammation, and weakening of the muscles that connect the joints. Decision-case scientific papers have been done in RSUD Kraton Pekalongan regency. It was conducted in April 2015. Physiotherapy diagnosis includes 1)  Impairment: the silent pain, tenderness and pain in the left knee motion; a decrease in muscle strength in the hamstring and quadriceps muscles; the limited range of motion. 2) Disability: the patient is unable to activity up and down the stairs, the patient is unable to walk long distances, the patient is unable to stand for long, the patient is unable to squat-stand. 3) Functional Limitation: Patients experiencing difficulties in toileting activities squat-stand for a long time and walk away, patients have difficulty climbingstairs, the patient is difficult to pray in a sitting position and the legs straight ahead. The purpose of physiotherapy management include reducing pain in the left knee joint, increases muscle strength ofthe left knee, increasing the range of motion of the left knee joint. Following the physiotherapy program as much as 5x, showed 1)knee pain from rest 3 to 1, press 3 to 2, and the motion of 4 to 3; 2)left knee muscle strength, m. hamstring and. Quadriceps from 3 to 4. 3)The scope of motion is increased inactivemotion, from 0˚-0˚-100˚-be-0˚ 0˚-110˚ 4)ADLno increase.